An investigation into the obstacles and Problems Faced by Libyan Learners in mastering English Pronunciation at the Intermediate Level - Ennas Mawloud Faraj Alharam, (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
Recently, it's been observed that understanding a language's phonological system significantly enhances learners' speaking abilities. Moreover, this knowledge greatly assists teachers in addressing many of their students' pronunciation challenges. This study emphasizes the importance of pronunciation learning and reviews relevant research and studies. It also discusses the factors that affect pronunciation. Additionally, the study examines specific pronunciation issues faced by Libyan learners at the intermediate level in private language centers. Although these learners work hard to improve their English proficiency, many struggle to achieve accurate pronunciation, which negatively impacts their communication skills and self-confidence. The research highlights several key obstacles, including interference from the Arabic sound system, limited exposure to native English pronunciation, and insufficient practice opportunities. Other problems relate to social and psychological factors such as fear of making mistakes, anxiety, self-confidence, motivation, and attitudes. The data for this investigation were gathered through a questionnaire specifically designed and administered to twenty-four intermediate-level Libyan learners. None of the participants had ever visited an English-speaking country. The collected data were subsequently analyzed to identify and understand the pronunciation challenges these learners face.